METODE BERMAIN PERAN TERHADAP KEMAMPUAN BAHASA EKSPRESIF ANAK TUNARUNGU - ASRINING INDAH, RIBUT (Jurnal Pendidikan Khusus, 2016)
ABSTRACT The deaf student have language development hidrance. From the observasi in SLB Tunas Kasih Surabaya at 16 Mei 2016 show that the deaf student to experience difficult to say and show object the want. To tell something the role playing methode used to surpass that. The purpose of this research is to analis the influence of role playing methode of ekspresif ability the deaf student in SLB Tunas Kasih Surabaya. This research used kuantitatif research with eksperimental appoximation. To match this appoximation. Therefore plan of research used single subject research with multiple baseline cross subjects desaign. The subject of research are there deaf student in SLB Tunas Kasih Surabaya. Data collage technich is observation and documentation Result off the research show that, the first subyek (NB) stabilitas level and baseline phase spin (A) 82% show stabil date with 1-2 spin, the second subject (OL) 87,5% show stabil date with 3-4 spin, and the third subject (NN) 85% show stabil date with 1-2 spin. Overlap presentase of the first subject (NB) is 11 %, second subject (OL) is 7 % and the third subject (NN) is 5%. It show the intervensi is influentual to target behavior. So that can be conclued there is significant influence in role playying methode of ekspresif ability the deaf student in SLB Tunas Kasih Surabaya.   Keywords: role playing methode, ekspresif ability